THE MAIN TASKS OF ECONOMIC POLICY (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
Economic policy plays a pivotal role in shaping the economic landscape of a nation. This article provides an overview of the main tasks of economic policy, highlighting the key objectives and tools used by governments to achieve them. The primary objectives of economic policy include promoting economic growth, ensuring price stability, reducing unemployment, and achieving income distribution. Additionally, this article explores the evolving challenges and considerations in economic policy, such as environmental sustainability and the impacts of globalization.